Analisis Kinerja Tim AMC dalam Pengelolaan Parking Stand Demi Keselamatan Penerbangan di Yogyakarta Internatinoal Airport - Shefa Willy Juniarto; Andi Syaputra (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Efficient management of aircraft parking stands is a critical element in maintaining flight safety at airports. As air traffic increases, the coordination and performance of the Apron Movement Control (AMC) team play a vital role in assigning parking positions to prevent operational delays and potential hazards. This study aims to evaluate the performance of the AMC team in managing parking stands at Yogyakarta International Airport using a descriptive qualitative approach. The assessment was based on five indicators proposed by Robbins & Judge: work quality, work quantity, timeliness, effectiveness, and independence. Data were collected through direct observation, semi-structured interviews, and documentation analysis. The findings indicate that the AMC team consistently performs its duties in accordance with established procedures, responds effectively to sudden operational changes, and demonstrates independent decision-making capabilities. These results highlight the crucial role of the AMC team in ensuring the safe movement of aircraft on the apron. However, challenges such as limited staffing and unanticipated schedule changes still require attention to improve overall operational efficiency.